2022
DOI: 10.3762/bjnano.13.57
|View full text |Cite
|
Sign up to set email alerts
|

A superconducting adiabatic neuron in a quantum regime

Abstract: We explore the dynamics of an adiabatic neural cell of a perceptron artificial neural network in a quantum regime. This mode of cell operation is assumed for a hybrid system of a classical neural network whose configuration is dynamically adjusted by a quantum co-processor. Analytical and numerical studies take into account non-adiabatic processes as well as dissipation, which leads to smoothing of quantum coherent oscillations. The obtained results indicate the conditions under which the neuron possesses the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…It should be noted that this system has proven to be a basic element of neural networks such as the perceptron with a sigmoidal input-to-output transformation function (sigma-neuron). Preliminary calculations have shown that under certain conditions, such a neuron can operate successfully in both classical and quantum modes [ 24 , 26 , 28 , 30 ]. The energy of the system in the Hamiltonian formalism can be expressed as follows:…”
Section: Model Of the Proposed Bifunctional Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that this system has proven to be a basic element of neural networks such as the perceptron with a sigmoidal input-to-output transformation function (sigma-neuron). Preliminary calculations have shown that under certain conditions, such a neuron can operate successfully in both classical and quantum modes [ 24 , 26 , 28 , 30 ]. The energy of the system in the Hamiltonian formalism can be expressed as follows:…”
Section: Model Of the Proposed Bifunctional Cellmentioning
confidence: 99%
“…According to the expressions in Equation 8 , the white dashed line in Figure 2c denotes the limit of the transition probability from the ground to the excited state P LZ < 0.01. This estimate is important for evaluating the functioning of this circuit in adiabatic quantum neural networks, where there are strict requirements for the absence of excitation from the initial state for the implementation of sigmoidal activation functions [ 30 ].…”
Section: A Bifunctional Superconducting Cell As a Controllable Flux Q...mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, in the field of quantum computing, the most efficient control of qubit states has been demonstrated for solid-state qubits. In the context of this work, we would like to highlight promising implementations of quantum bits (qubits) which are based on the general features of the energy spectrum of the double-well potential [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. In various flux qubits and double quantum dots, tunneling splitting of the ground state allows the formation of a qubit basis.…”
Section: Introductionmentioning
confidence: 99%
“…- Implementation of Josephson junctions for the design of quantum computers by analyzing the dynamics of a single-junction superconducting interferometer as an adiabatic neural cell of a perceptron artificial neural network in the quantum regime (a hybrid system whose configuration is dynamically adjusted by a quantum co-processor) [ 23 ].…”
mentioning
confidence: 99%